Career trajectories of women faculty who became academic administrators - Vancour, Michele L. (Advancing Women in Leadership Journal, 2023)
Women faculty often view academic leadership as incompatible with their work-life balance, detracting from research and teaching commitments, resulting in a loss of autonomy and an abandonment of discipline, promoting change in their relationships with colleagues, and placing an increased emphasis on budgeting, regulations and compliance (DeZure et al., 2014). Many researchers suggest that institutional culture works against leadership development for faculty, making the transition from faculty to administrator unlikely (Barden & Curry, 2013). It is increasingly important to identify the key factors that make the difference for women faculty to assume these roles. As such, in this study qualitative methods were employed to examine the experiences and career trajectories of 16 academic women who held tenured, fully promoted faculty positions prior to becoming administrators. The researcher found evidence to support future recruitment and retention in higher education leadership.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed